Multi-channel Integration: Factor Driving Satisfaction and Customer Loyalty in the Omni-channel Retailing - Dessy Yunita; Mohamad Adam; Zakaria Wahab; Isni Andriana; Ahmad Maulana; Iisnawati Iisnawati (University of Merdeka Malang, 2022)
Multi-channel integration is a prerequisite for omni-channel retail success. Implementation of good multi-channel integration increases satisfaction and has an impact on long term relationships with customers, one of which is customer loyalty. This research was conducted in a retail department store in the city of Palembang, namely Matahari Department Store (MDS). This study distributed questionnaires to 200 respondents who were buyers at MDS on at least two channels owned by MDS. The data analysis technique uses path analysis with the help of SPSS. The results show that multi-channel integration indirectly affects customer loyalty through satisfaction.